2015
DOI: 10.4103/0366-6999.150111
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Treatment Strategy for Patients with Diffuse Large B-Cell Lymphoma after First-Line Therapy

Abstract: Background:Rituximab in combination with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) significantly prolonged event-free survival in first-line chemotherapy for patients with diffuse large B-cell lymphoma (DLBCL). But relapse and refractory DLBCL occur frequently. Although rituximab is effective, its role in salvage therapy after autologous transplant remains unclear. Maintenance therapy with rituximab in responding patients after first line chemotherapy may be a useful novel approach capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…The efficacy of rituximab as maintenance therapy in DLBCL was previously evaluated in 3 meta-analysis of RCTs. [24][25][26] One meta-analysis by Nannya et al 24 The third meta-analysis, published by Zhou et al, 26 included 5 RCTs 2, [16][17][18]27 and concluded that males and previously untreated DLBCL patients benefited most from maintenance treatment in terms of EFS and PFS when rituximab was the maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of rituximab as maintenance therapy in DLBCL was previously evaluated in 3 meta-analysis of RCTs. [24][25][26] One meta-analysis by Nannya et al 24 The third meta-analysis, published by Zhou et al, 26 included 5 RCTs 2, [16][17][18]27 and concluded that males and previously untreated DLBCL patients benefited most from maintenance treatment in terms of EFS and PFS when rituximab was the maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…included 4 RCTs,2,17,18 of which one included patients after autologous stem cell transplantation 27. This meta-analysis demonstrated that males had a higher EFS and lower rate of adverse effects compared to females when rituximab maintenance was administered, and that rituximab improved EFS only when it was not used also in the induction phase.The second meta-analysis published by Ren et al25 included 3 RCTs using rituximab maintenance, 2,17,18 and 4 RCTs using rituximab therapy as part of the salvage chemotherapy in the relapse setting and not as maintenance. This meta-analysis demonstrated that maintenance therapy with rituximab had no statistically significant effect on OS or EFS.…”
mentioning
confidence: 99%
“…The National Comprehensive Cancer Network-International Prognostic Index for diffuse large B-cell lymphoma (DLBCL) could be a good example for our deduction, which has stronger prognostic value compared with original IPI for patients treated in the rituximab era who have an ameliorated outcome. [910] Furthermore, all the 5000 patients in the original IPS study were from western countries. Whether IPS applies to Chinese people remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…84 Another meta-analysis included seven studies of 1470 patients with DLBCL who received maintenance rituximab following chemoimmunotherapy induction and in the salvage setting. 85 Rituximab maintenance statistically improved EFS but not OS. Taken together, these results do not justify the administration of rituximab maintenance after induction treatment with standard R-CHOP.…”
Section: Rituximabmentioning
confidence: 97%